Ecuadorian biochar with energy potential - Quesada-González, Omaida; Cantos-Macías, Manuel A.; Duharte-Rodríguez, Wendy Lucía; Cascaret-Carmenaty, Dannis Adrian; Rodríguez-Matos, Josefina (Revista Cubana de Química, 2022)
The pyrolytic cracking of forest residues is a complex process that determines the characteristics of the biochar obtained. The objective is to specify through experimental design, the experimental variables that influence the pyrolysis of sawdust from Ecuadorian Teak, Fernán Sánchez and Guachapelí woods and their most favorable values to achieve higher yields in this process, so that it allows elucidating a Experimental procedure for obtaining biochars, as well as their characterization. The applied experiment design showed that temperature is the only parameter that significantly affects pyrolysis and allows us to propose an experimental procedure to obtain biochar. The SEM and the FT-IR of the biochars demonstrate the effectiveness of the process and the EDX of the biochars obtained show a stoichiometric ratio of C/O 5:1 enriched in charcoal, as well as the elemental composition of its ashes.